Supermarket Own Brands, Supply Chains and the Transformation of the Agri-food System - Burch, David; Lawrence, Geoffrey (The International Journal of Sociology of Agriculture and Food, 2005)
The growth in consumption of supermarket ‘own brand’ food lines is having a significant impact on the organization and management of agri-food supply chains. In past decades, first-generation supermarket own brands were usually produced by established processing companies, which simply put a supermarket label on food lines already being marketed as branded products. Today, many own brand products are being produced for the supermarkets by newly-emerging specialist processing companies which manufacture nothing but supermarket lines. These specialist processing companies, which comprise an important element of the new supply chains established by globalizing supermarkets, utilize just-in-time techniques and flexible production systems to supply a range of innovative food lines, from home-prepared meals to fresh, unprocessed, foods. Their emergence signifies a profound shift in the system of provisioning, which can be linked to wider changes accompanying globalisation. This paper explores the theoretical and policy implications of such changes, and argues that they foreshadow the emergence of a third food regime.